2013
DOI: 10.1615/intjmedmushr.v15.i4.10
|View full text |Cite
|
Sign up to set email alerts
|

Royal Sun Medicinal Mushroom, Agaricus brasiliensis Ka21 (Higher Basidiomycetes), as a Functional Food in Humans

Abstract: The Royal Sun medicinal mushroom, Agaricus brasiliensis, is used as a natural health product. In Japan, however, the quality control of some of these mushroom products has been viewed as a safety problem. Focusing on the quality control of A. brasiliensis KA21, we have performed several safety studies. To date, we have established evidence that this mushroom can be used safely as an immunostimulant and to mediate biochemical parameters associated with obesity or diabetes. Furthermore, to improve the manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Agaricus brasiliensis Ka21, a type of higher Basidiomycete, is deemed to be a safe immunostimulant mediator of biochemical parameters relevant to diabetes and obesity. Safety studies of A. brasiliensis Ka21 have been carried out to confirm its safety as a functional food (Yamanaka et al, 2013).…”
Section: Research On the Application And Limitations Of Mushroom Polymentioning
confidence: 99%
“…Agaricus brasiliensis Ka21, a type of higher Basidiomycete, is deemed to be a safe immunostimulant mediator of biochemical parameters relevant to diabetes and obesity. Safety studies of A. brasiliensis Ka21 have been carried out to confirm its safety as a functional food (Yamanaka et al, 2013).…”
Section: Research On the Application And Limitations Of Mushroom Polymentioning
confidence: 99%
“…The contents of -glucan in mushrooms vary according to the growing conditions, such as soil, climate, and season Suga, 2004 . Agaricus brasiliensis KA21 grown in open culture is more nutritious than that grown in greenhouses Yamanaka et al, 2013 . In the present study, an extract of Agaricus brasiliensis was found to exhibit antiviral effects on influenza virus in vitro. Substances that serve as active centers of Agaricus brasiliensis need to be identified in future studies.…”
mentioning
confidence: 48%
“…Performed studies on murine models and human volunteers to examine the immuneenhancing effects of the naturally outdoor-cultivated fruit body of A. brasiliensis KA21 (i.e. Agaricusblazei) has shown antitumor, leukocyte-enhancing, hepatopathy-alleviating and endotoxin shockalleviating effects in mice [23][24][25]. In the human study, percentage body fat, percentage visceral fat, blood cholesterol level and blood glucose level were decreased and natural killer cell activity was increased.…”
Section: Agaricus Subrufescens (Peck)mentioning
confidence: 99%